Vzaimosvjaz' trenirovocnych nagruzok s metaboliceskim otvetom organizma biatlonistok vysokoj kvalifikacii - Sinicenko, R. P. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
The article presents the results of the analysis of the relationship between the indicators of actually performed training loads and the metabolic response parameters of the organism of elite biathletes on the basis of biochemical control data. Revealed às a result of the study, statistical interrelationships of training loads with the metabolic response of an athlete`s body can be used to develop individual training plans for athletes and to effectively manage the training process of biathletes in general.